ANALISIS FAKTOR YANG MEMPENGARUHI PERUBAHAN UPACARA PERKAWINAN ADAT JAWA(SOLO) DI DESA KEPENUHAN JAYA KECAMATAN KEPENUHAN HULU KABUPATEN ROKAN HULU - Sulis Riyanti; Sri Erlinda; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine whether there are changes in the implementation of traditional Javanese wedding ceremony (solo) and the factors that affect changes in traditional Javanese traditional marriage ceremonies (solo) di Desa Kepenuhan Jaya Kecamatan Kepenuhan Hulu Kabupaten Rokan Hulu. Respondents in this study was 43 patriarch and 2 people pinisepuh (the elder). Data collection techniques are observation, interviews, questionnaires, and documentation. The method used is the method of combination of quantitative and qualitative (mixed methodes). This method is done with the data processing data results are presented through the calculation of the percentage and given an explanation. The results showed that Based on the research that the author carried on the analysis of the factors affecting changes in the marriage ceremony traditional Javanese (solo) di Desa Kepenuhan Jaya Kecamatan Kepenuhan Hulu Kabupaten Rokan Hulu is that the implementation of the marriage ceremony traditional Javanese (solo) is still carried out is the consent granted, Adicara Sungkeman, determine the marriage ceremony, the ceremony Panggih temanten, lamaran,ceremony ngidak tigan lan wijik sekarsetaman,ceremonytukar cincin and Srah-srahan,asrah sangganlan kembar Mayang ceremony and buncalan adicara ceremony. And factors affecting changes in Javanese traditional marriage (solo) is a confounding factors inter-tribal / inter-marriages, heterogeneous population factor, contacts with other cultures, other public cultural influence, economic factors, the time factor, Factor technology.Keyword : the Factor Effect, changes, the marriage ceremony traditional Javanese